Service quality of e-Commerce logistics services - SANKAR, DR. JEGANATHAN GOMATHI; MR. GOPALAKRISHNAN T (The journal of contemporary issues in business and government, 2020)
The research paper titled the service quality in E-commerce logistics services. The objective of the study is to identify the factors that influence service quality in the E-commerce logistics industry. causal research design is used in the study as the research design and the sampling method used is convenience sampling. The sample size of the study is 85 respondents and it is analyzed using the SPSS tool. The collected data were analyzed with statistical tools such as frequency analysis and Regression analysis. It is found that factors affecting customer satisfaction are packing factor, communication factors, delivery speed and quality factor. Among the factors, The packing factor has a strong positive linear relationship with customer satisfaction.